(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
The expediency of membrane processing of pectin extracts in the mode with vibration mixing is substantiated. The influence of temperature, pressure and duration of the process of membrane concentration and purification of pectin extracts on the characteristics of ultrafiltration membranes of the PAN type has been established. Rational parameters and regimes of the process of ultrafiltration concentration and purification of pectin extracts have been determined.